Is Religious Belief a Kind of Belief? - Crane, Tim 1962- (2023)
This paper discusses the familiar question of whether expressions of faith or conviction offered by religious believers really express their beliefs, in the standard sense of "belief" used in philosophy and psychology. Some hold that these expressions do not express genuine beliefs because they do not meet the standards of rationality, coherence and integration which govern beliefs. So they must serve some other function. But this picture of "genuine belief" is inadequate, for reasons independent of the phenomenon of religion. Once we get a better picture of belief, we can see that religious beliefs conform to this picture, and that typical expressions of faith really are expressions of belief in the proper sense.
In diesem Beitrag wird die bekannte Frage erörtert, ob die von religiösen Gläubigen geäußerten Glaubens- oder Überzeugungsbekundungen tatsächlich Ausdruck ihrer Überzeugungen im Sinne des in der Philosophie und Psychologie verwendeten Begriffs "Überzeugung" sind. Einige sind der Meinung, dass diese Äußerungen keine echten Überzeugungen ausdrücken, weil sie nicht den Standards der Rationalität, Kohärenz und Integration entsprechen, die für Überzeugungen gelten. Sie müssen also eine andere Funktion erfüllen. Dieses Bild des "echten Glaubens" ist jedoch aus Gründen, die nichts mit dem Phänomen der Religion zu tun haben, unzureichend. Wenn wir uns ein besseres Bild vom Glauben machen, können wir sehen, dass religiöse Überzeugungen diesem Bild entsprechen und dass typische Glaubensbekundungen tatsächlich Ausdruck von Überzeugungen im eigentlichen Sinne sind.
Keywords: Rationalität; Realismus in Bezug auf Überzeugungen; Religious Belief; Religiöse Überzeugung; inferential integration; logische Integration; propositional attitudes; propositionale Einstellungen; Rationality; realism about beliefs